How a 7-Week Food Literacy Cooking Program Affects Cooking Confidence and Mental Health: Findings of a Quasi-Experimental Controlled Intervention Trial - Rees, Joanna; Fu, Shih Ching; Lo, Johnny; Sambell, Ros; Lewis, Joshua R.; Christophersen, Claus T.; Byrne, Matthew F.; Newton, Robert U.; Boyle, Siobhan; Devine, Amanda (Frontiers in Nutrition, 2022)
Obesity and mental health disorders are rising simultaneously with shifting dietary behaviour away from home cooking, towards typically nutrition-poor and energy-dense convenience meals. Food literacy strongly influences nutrition choices. Community-based cooking interventions target barriers to healthy eating and facilitate development of food literacy skills, thereby potentially increasing preparation of home-cooked meals and positively influencing health. This study of healthy Australian adults explored the efficacy of a 7-week cooking program in improving cooking confidence, whether this transferred to behaviour surrounding food, and/or affected mental health. Significant post-program improvements in cooking confidence and satisfaction (all p<0.001, η2p 1.12 large), ability to change eating habits (p<0.001) and overcome lifestyle barriers (p=0.005) were observed for the intervention group but not control. Participation also improved mental and general health (all p<0.05, η2p 0.02 small). No changes were observed for acquisition and consumption of food, or nutrition knowledge in either group. This 7-week cooking program built cooking confidence and improved general and mental health but did not change dietary behaviour. To further improve nutrition related behaviours associated with better mental health, more effort is needed to recruit those with below-average nutrition knowledge and interest in cooking.